Experimental Gasification of Coffee Husk Using Pure Oxygen-Steam Blends - Bonilla, Javier; Gordillo, Gerardo; Cantor, Carlos (Frontiers in Energy Research, 2019)
This work discusses results on temperature profile, syngas composition, High Heating Value, and efficiency of a Coffee Husk counter-current fixed-bed gasification process, in which oxygen-steam blends were used as oxidizing agent. The experimentation was carried out for various Equivalence Ratio (ER) and Steam-Fuel Ratio (SF), whose ranges were [1.6 – 5.6] and [0.4 – 0.8] respectively. The results show that Increased steam (higher steam fuel ratios) improves the H2/CO molar ratio i.e., for a constant ER=3.7 and SF at 0.4, 0.6, and 0.8, the H2/CO ratio was 1.2, 1.4, and 1.8 respectively. Also, the addition of steam tends to increase the syngas Higher Heating Value, which ranged between 7714 kJ/m3 at ER = 1.6 and SF = 0.4 and 8841 kJ/m3 at ER = 3.2 and SF = 0.8. On the other hand, increased ER (lower oxygen) decreases the Net Cold Gasification Efficiency (CGENET) which was between 53 % at ER = 5.6 and SF = 0.6 and 82 % at ER = 1.6 and SF = 0.4. Results were also compared to results published before for gasification of the same biomass but using air-steam mixtures for partial oxidation. This comparison shows that the use of oxygen increases both the temperature profile in the bed and the yield of CO and H2 contained in the syngas.